Poetic Structure and Arts of Prose in Modern Arabic Literature: الأشكال الشعرية والفنون النثرية في الأدب العربي الحديث - Jahantab, Zakira (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
الأدب هو شكلٌ من أشكال التعبير عن مشاعر الإنسان وعواطفه، وهو أسلوبٌ من الأساليب التي يستخدمُها الإنسان لإفراغ هواجسِه وخواطره وعرض أفكاره بمساحة يخلقُها لنفسه من الحروف، ويُعرَفُ الأدب في كلِّ لغة من لغات الأرض بأنّه مجموعة النصوص التي كتبها الأدباء والشعراء حول العالم بهذه اللغة، وتختلف فنون الأدب في كلِّ اللغات؛ فمن الأدباء من يعبّر عن أفكاره ومشاعره شِعرًا، ومنهم من يعبّر عن ذلك نثرًا، وللنثر أنواعٌ أيضًا، وهذا التنوّع في هذه الفنون قائمٌ على الأدوات التي يمتلكها كلُّ كاتب، وعلى الميول الأدبيّة الخاصّة به، كما اتخذ الأدب في العصر الحديث في العالم العربي منحى جديدًا بدخول مجموعة من الفنون الأدبية العربية الجديدة على الأدب، لم تكن هذه الفنون معروفة من قبل أو سائدة عند الأدباء العرب، دخل الفنّ المسرحي النثري والشعري لأول مرة في تاريخ الأدب العربي كلِّه، فقد تطورت الدراسات النقدية في العصر الحديث و اكتشف النقاد عوالمَ أخرى في النص الأدبي العربي ورصدوا تطورات النص الأدبي عبر العصور، وفصَّلوا في المعجم اللغوي والدلالي في كلِّ نص أدبي، فمنحوا النقد مساحات إضافية ونظريّات نقدية جديدة لم تكن معروفة ومتداولة في عصور الأدب السابقة، وهذا المقال سيسلِّط الضوء على الأدب في العصر الحديث بفنونِه المختلفة. الكلمات المفاتيح: الأدب، العصر الحديث، مشاعر، نثرًا، الفنّ الشعري، ونظريّات نقدية. Abstract Literature is a form of expression of human feelings and emotions, and it is one of the methods that a person uses to express thoughts and present his ideas with a space that he creates for himself from words, and literature is known in every language of the earth as the set of texts written by writers and poets around the world in the language, and the arts of literature differ in all languages; Some writers express his thoughts and feelings in poetry, and some express it in prose, and prose has types as well, and this diversity of art is based on the tools and on his own literary tendencies that each writer possesses, and literature in the modern era in the Arab world has taken a new turn with the recognization of new Arab literary arts to literature, these arts were not known before or prevalent among Arab writers. Theatrical prose and poetic art recognized for the first time in the entire history of Arab literature. The Studies of Criticism have developed in the modern era and critics discovered other worlds in the Arabic literary text and monitored the developments of the literary text through the ages and explained the linguistic and semantic lexicon in every literary text. These studies have given criticism additional areas and new critical theories that were not known and circulated in previous literary eras, and this article will highlight on literature in the modern era with its various arts. Keywords: Literature, modern era, emotions, prose, poetic art, critical theories.